An Analysis of Erich Fromm's Views on the Relationship Between Religion and A Personality - Malikov, Aladdin; Məmmədov, Azad (Scholarya Demo Journal of Ruby, 2020)
Fromm’s views on religion occupy an important place both in terms of the development of religious psychology and the significance of religion in psychology. The article deals with Erich Fromm’s general views on religion and demontrates the relationship between religion and personality. This relationship can be both negative and positive. Moreover, it is not the structure of a particular religion that does matter, but the extent to which some religion is human-oriented, in other words, its humanistic character. Thus, the religions help people develop and use their talents. The personality formation is considered an indicator of human development. According to Fromm, the degree of religiosity affects a person. Religions can affect a person both negatively and positively. In this regard, Fromm subdivides all religions into two groups: these are authoritarian religions and humanistic ones. Describing his religious views, he indicated the religions that guide a person, contributing to his development. These religions are developing and true. They have a positive impact, and Fromm calls them humanistic religions. In authoritarian religions, a person is helpless before God, his will has no meaning and does not play any role. Man becomes virtuous simply following the will of God. This is the greatest virtue. Man here loses his personal freedom and integrity, obeying and clinging to God. Therefore, authoritarian religions complicate human existence and hinder personality’s development. In all authoritarian religions, God is endowed with absolute power and control over man. That is why a person feels powerless and worthless before God.